Growing connection beyond prison walls: How a prison garden fosters rehabilitation and healing for incarcerated men. Issue 5 (4th July 2019) - Timler, Kelsey; Brown, Helen; Varcoe, Colleen
Abstract: Correctional agriculture and gardening have become more popular in recent years, and evidence points to physical, social and mental health benefits, as well as impacts on inmate rehabilitation and recidivism. Many correctional agriculture programs focus on the benefits of growing fruits and vegetables, using resulting produce to offset institutional costs. In contrast, a prison garden program in Canada engages incarcerated men in not only the growing but the subsequent donating of produce to food insecure and economically vulnerable communities. A qualitative study of the program impacts highlights the benefits of the garden program on participating men. We outline the positive impacts associated with the planting, tending and harvesting of food, as well as the benefit associated with giving back and doing good through the donation of food to local communities. While growing food in prison is beneficial, providing opportunities to donate that food and to nurture connection between growers and recipients has impacts for incarcerated people far beyond the immediate benefits of gardening. These benefits include supporting the self-esteem and self-worth necessary to imagine a future shaped by the experience of giving back through meaningful work. Implications for correctional programming and research are discussed.